NEPAD Partnership with the Federal Government of Nigeria: A Path to Peace and Stability - Sampson, Osevwe Enoh; Kuma, Lanem Law; Allam, Michelle Dooshima (Kashere Journal of Politics and International Relations, 2025)
The NEPAD has provided avenue for peace and security development in Nigeria and indeed Africa. Thus, her role in peace building has become relevant to our country at the federal level. This work seeks to look at those areas where NEPAD can partner not just with federal government alone but also with the private sector in order to promote peace and security sustainability in Nigeria. The work therefore, has provided the needed avenue where NEPAD and the federal government partnership can improve the socio-political and socioeconomic development of the Nigerian State.